Currency Board Arrangements : Issues and Experiences - Enoch, Charles; Balino, Tomas (Washington, D.C. : International Monetary Fund, 1997)
This paper provides a comprehensive analysis of the attractions and disadvantages of currency board arrangements in their various institutional configurations. It asks what defines a currency board arrangement, what are their strengths and weaknesses, and what constraints they place on macroeconomic policies. It also reviews country experiences with these arrangements.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet